2021
DOI: 10.3389/fimmu.2020.625833
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Through Nucleic Acid Sensors and Their Roles in Inflammatory Diseases

Abstract: Recognition of pathogen-derived nucleic acids by pattern-recognition receptors (PRRs) is essential for eliciting antiviral immune responses by inducing the production of type I interferons (IFNs) and proinflammatory cytokines. Such responses are a prerequisite for mounting innate and pathogen-specific adaptive immune responses. However, host cells also use nucleic acids as carriers of genetic information, and the aberrant recognition of self-nucleic acids by PRRs is associated with the onset of autoimmune or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 258 publications
(310 reference statements)
0
51
0
Order By: Relevance
“…The cytosolic RNA-sensing signaling pathway is an important antiviral innate immune mechanism that responds to invading viral RNAs, leading to type I IFN and interferon stimulated gene (ISG) expressions ( 1 , 2 ). Deregulation of this signaling pathway may result in autoimmune diseases if it reacts to cellular self RNAs ( 3 , 4 ). It has been found that deficiency of the RNA-editing enzyme ADAR1 activates this innate immune signaling pathway and enhances ISG expression in mouse embryos ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cytosolic RNA-sensing signaling pathway is an important antiviral innate immune mechanism that responds to invading viral RNAs, leading to type I IFN and interferon stimulated gene (ISG) expressions ( 1 , 2 ). Deregulation of this signaling pathway may result in autoimmune diseases if it reacts to cellular self RNAs ( 3 , 4 ). It has been found that deficiency of the RNA-editing enzyme ADAR1 activates this innate immune signaling pathway and enhances ISG expression in mouse embryos ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through knock-out of IFNAR, we found the B cell intrinsic action of type I IFN to be expendable for their GC participation. In addition, the two signaling pathways converge, albeit ostensibly via different routes, on the activation of MAPK/AP-1 and NF-κB, which promote production of proinflammatory cytokines, survival, and proliferation of the cell ( 54 ). Despite their downstream overlap in effector functions, the TLR7 and STING pathways are compartmentalized very differently in the host cell, with topological equivalence and inequivalence, respectively, to the subcellular localization of the BCR.…”
Section: Discussionmentioning
confidence: 99%
“…The immunogenic property of mRNA is both beneficial and detrimental for mRNA vaccines. The presence of nucleic acid sensors, such as TLR3, TLR7/8, RIG-I, and MDA-5, recognize vaccinated mRNA, which then proceed to activate innate immune signaling pathways to produce type-I IFNs (Okude et al, 2020). As mentioned previously, activation of innate immunity is crucial for the development of adaptive immunity against the intended vaccine target.…”
Section: Mrna Vaccines and Adjuvantsmentioning
confidence: 99%